Daryono's artistic creativity journey in the body of Surakarta Style Javanese Dance - Lambangsari, Sonia Pangesti; Widyastutieningrum, Sri Rochana; Setiawan, Aris (Institut Seni Indonesia Surakarta, 2023)
This study aimed to explore the Daryono’s artistic, creative journey in the body in the Surakarta Style of Javanese Dance. The research method was carried out through observation of dance performances presented by Daryono, that is, Beksan Diradameta. Through this dance, the researcher studied the form and characteristics of Daryono's dance expertise. The observation focused on the process of achieving the quality of Daryono dance through various stages. In-depth interviews were conducted to reinforce the data obtained through the observation. The results showed that the factors and stages that were passed caused Daryono's expertise in Javanese dance, Surakarta style, to reach taksu. The stages are mastery of techniques, formation of the body, spiritual mastery, and awareness of philosophical concepts. On spiritual and philosophical principles, Daryono has always adhered to the concepts of Hasthasawanda, Joged Mataram, Mandala, and Asta Brata. This research can contribute to the development of artistic knowledge, especially Javanese dance in the Surakarta style.